2011
DOI: 10.1177/1078390311426454
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Psychobiological Predictors of Psychological Response to Childbirth

Abstract: The associations found in this study can improve identification during pregnancy of women at risk for negative psychological response to childbirth. For these women, the provision of supportive care during pregnancy should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…This result suggests that the disruption on this cortisol basal rhythm [ 73 ] consequence of the elevated cortisol levels by bedtime may be related with the dynamic of the awakening response. Indeed, previous research has documented the association between the CAR and psychological outcomes, such as anxiety, depression or work stress [ 14 , 31 , 41 , 42 , 80 ] or during pregnancy, as related with fear regarding the anticipation of childbirth [ 2 ]. Therefore, CAR is very likely to be sensitive to chronic stress and its anticipation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that the disruption on this cortisol basal rhythm [ 73 ] consequence of the elevated cortisol levels by bedtime may be related with the dynamic of the awakening response. Indeed, previous research has documented the association between the CAR and psychological outcomes, such as anxiety, depression or work stress [ 14 , 31 , 41 , 42 , 80 ] or during pregnancy, as related with fear regarding the anticipation of childbirth [ 2 ]. Therefore, CAR is very likely to be sensitive to chronic stress and its anticipation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Untreated antenatal depression can be associated with risk of postpartum depression, which has significant consequences for the health and well-being of the infant [ 2 ]. Antenatal depression is a public health concern due to its negative effect on the general health of the woman and its association with underutilization of antenatal care services, complications during pregnancy, negative experience of childbirth, adverse pregnancy outcomes (e.g., preterm birth, low birth weight, still birth, and birth asphyxia), and infant mortality and morbidity (i.e., poor infant growth and development) [ 3 7 ]. Moreover, the magnitude of the impact of antenatal depression varies across socioeconomic status [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that FoC negatively affects women in a number of ways, including sleep disturbance and depression in pregnancy [13], increased health care use during the perinatal period [14], requests for medical interventions such as an elective caesarean section, a priori request of epidural analgesia without pain experience [1518], negative experience of childbirth, postpartum depression, post-birth trauma [1921], and low rates of breastfeeding [22, 23]. Negative effects of FoC are also associated with increased incidence of small gestational age (15 %), increased preterm birth rate (12 %), infant admission to intensive care [24, 25] as well as poor quality of infant’s sleep [26].…”
Section: Introductionmentioning
confidence: 99%